PENGARUH POLA KOMUNIKASI KELUARGA TERHADAP PERILAKU AGRESIF ANAK - Muhammad Nabil Sultan Athallah (2024)
This research is entitled 'The influence of family communication patterns on children's aggressive behavior'. Using the Family Communication Patterns Theory which is based on conformity orientation and conversation orientation, the types of family communication patterns can be categorized by looking at high or low conformity orientation and conversation orientation, the first is the consensual family communication pattern which has a high conformity orientation and a high conversation orientation. , then a pluralistic family communication pattern which has a low conformity orientation and a high conversation orientation, then a protective family communication pattern which has a high conformity orientation and a low conversation orientation, and a laissez-fair family communication pattern which has a low conformity orientation and a low conversation orientation. low conversation. The data results from the survey are then processed using descriptive analysis and inferential analysis, where descriptive analysis explains the characteristics of the respondents and analyzes variable X and variable Y. Then for inferential analysis a linear regression test, coefficient test and hypothesis test are carried out. This research has data analysis test results that support this research can accept H1, which means there is an influence between family communication patterns on children's aggressive behavior.